Pembelajaran 3D Printing sebagai metode perancangan produk kostum (Studi Kasus: industri cosplay) - Putri Anggraeni Widyastuti (PRODUCTUM Jurnal Desain Produk (Pengetahuan dan Perancangan Produk), 2020)
Currently costume products can be enjoyed not only for film, drama or theater productions but for people as a form of appreciation to the fictional and non-fictional characters in two dimensions. Cosplay (abbreviation of a word: costume and play) in Indonesia has developed into a industry within a period of 15 year due customer needs. Even as cosplayer (people who cosplay) who has long been active in cosplaying, develop tecniques and the use of the material in process of designing cosplay costumes until introduce profession cosmaker (an abbreviation of costume maker). They have needed experience to cultivate material and technique that support skill of cosplayer and cosplayer craft’s to design costume for custom or mass, like 3D printing. This technique have been used to simplify the design process costume because efficiently and with more having the accuracy of finite dimensionnal produce of the successive visual better. For this reason, this research is needed with the aim that 3D printing can be a part of and enrich the design of costume products so that it can take part of basic in learning basic education design. This purpose will achieve through the qualitative study in a series of stage of the methodology grounded theory to declare that 3D printing can be a part in learning basic education design to answer the challenges the industrial revolution 4.0 through phenomenology approach to phenomena cosplay in Indonesia for 15 year who experienced by writer directly design cosplay costume.Key words: 3D printing, Indonesia cosplay industry, method of design, learning, costume product